Primary diffuse leptomeningeal melanomatosis in a child with a clinical presentation mimicking meningitis: case report and review of literature - P. V. Sudharsan; Jeena Joseph; Krishna Prabhu Raju; Geeta Chacko (Egyptian Journal of Neurosurgery)
Abstract Primary diffuse leptomeningeal melanomatosis (PDLM) is a rare and malignant form of melanoma, with an incidence of one in ten million. It most commonly occurs in the fourth decade of life and is even rarer in pediatric populations. Due to its nonspecific clinical presentation, it is often misdiagnosed as tuberculous meningitis or hemorrhage. The pre-operative diagnosis of PDLM prior to surgery is highly challenging and is usually confirmed through biopsy, as cutaneous lesions are not commonly present. We present the case of a 7-year-old boy who exhibited symptoms of raised intracranial pressure and fever, which mimicked an infective etiology but was ultimately diagnosed with primary diffuse leptomeningeal melanomatosis, a histological surprise.